Aspects linguistiques du stéréotype de l’Allemand dans les comédies françaises des années 1960 - Nedjma Moussaoui (Mise au Point)
Comedy exaggerates, and its comical dimension is often strongly rooted in geography: that is why comedy, as a genre, is widely open to hosting national stereotypes of foreigners. From 1960 on it is possible to observe that a number of French comedies, often European co-productions, feature the stereotype of the German, in the construction of which linguistic habits play a specific role. Fifteen years after the Second World War, they show a meaningful evolution in the representation of the German with regard to a both national and european identity.